Meta-Analysis of the Effect of Cognitive Activity Exercise on Independence Ability in Post-Stroke Patients - Aktovianta, Lukman; Murti, Bhisma; Adriani, Rita Benya (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: A stroke is an attack on the brain that occurs when the blood supply to part of the brain is blocked so that part of the brain becomes damaged and dies because it does not get nutritional intake. Cognitive exercise activities can maintain optimal blood flow and improve the delivery of nutrients to the brain. The study aims to analyze the effect of cognitive exercise activity on the independence ability in post-stroke patients.Subject and Method: The study was a meta-analysis with PICO as the following: Population: post-stroke patients. Intervention: cognitive exercise activity. Comparison: no cognitive exercise activity. Result: independence ability. The articles used in this study were obtained from three databases, namely Google Scholar, PubMed, and ScienceDirect. The keywords for searching for the articles were